PENGGUNAAN VARIASI MEDIA PADA PEMBELAJARAN PKn UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK DI KELAS IV MIN ADAN BEUREUNUEN - Nurfajriyanti Nurfajriyanti (Jurnal Pesona Dasar, 2021)
In accordance with the demands of the development of technology and information teachers are required to innovate in learning, one of them teachers should master the various uses of media in learning. The problems examined in this study are how the activities of teachers and students in the use of media variations and whether the use of media variations in Civics material can improve student learning outcomes in class IV MIN Adan Beureunuen. This study aims to see the activities of teachers and students in using media variations on the Civics material to improve student learning outcomes in class IV MIN Adan Beureunuen. The approach used in this study is qualitative with a type of classroom action research (CAR). Data collection is done by observation and tests. Observations were made to see the use of variations in the media in the learning process, while the test to see student learning outcomes. Furthermore, all data is processed using a percentage formula. The results of the first cycle showed that there were still many shortcomings. Both in terms of the media, teachers, and student activities. So the learning outcomes of students in the first cycle under the KKM. So it continues in the next cycle. In cycle II shows that there are better changes in the media, teacher activities, and students. So that student learning outcomes increase. In the first cycle the teacher's activity reached 90% with a very good category, but in the second cycle it had increased to 96% with a very good category too. In the first cycle the activity of students reached 66% in the good category, but in the second cycle it had increased to 79% in the very good category. Likewise in cycle 1 learning outcomes 52% of students are complete and in cycle II it increases to 79% which is complete. This means that the use of media variations can improve student learning outcomes in grade IV MIN Adan Beureunuen.